The Role of Academic Supervision and Communication on Teacher Performance - Wardani, Ratih Kusuma; Santosa, Heru; Rahmawati, Desi (Journal of Education Research and Evaluation, 2021)
The purpose of this study was to obtain information about the role of academic supervision and interpersonal communication. research place at public elementary schools in the administrative city of South Jakarta. This study used a survey method with path analysis techniques and a causal quantitative approach. The sample in this study was 81 teachers who were taken using simple random sampling technique or simple random sampling and the teachers who were the object of the research were determined using the sample technique formula from Slovin. The data analysis technique was performed using descriptive and inferential statistics by first doing the prerequisite analysis, namely population normality and regression analysis. The findings from the study that academic supervision activities and smooth interpersonal communication play a major role in improving teacher performance. Professional teachers will be able to manage learning activities well and will be able to provide motivation to students so that the goals of learning will be achieved and produce students who excel in their respective fields.